2013
DOI: 10.1021/bc400236n
|View full text |Cite
|
Sign up to set email alerts
|

Conjugates of Amino Acids and Peptides with 5-O-Mycaminosyltylonolide and Their Interaction with the Ribosomal Exit Tunnel

Abstract: During protein synthesis the nascent polypeptide chain (NC) extends through the ribosomal exit tunnel (NPET). Also, the large group of macrolide antibiotics binds in the nascent peptide exit tunnel. In some cases interaction of NC with NPET leads to the ribosome stalling, a significant event in regulation of translation. In other cases NC-ribosome interactions lead to pauses in translation that play an important role in cotranslational folding of polypeptides emerging from the ribosome. The precise mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
(79 reference statements)
0
13
0
Order By: Relevance
“…Binding affinities of CAM-derivatives to E. coli ribosomes was analyzed by competition binding assay using fluorescently-labeled BODIPY-ERY as described before [26, 27, 37]. BODIPY-ERY (4 nM) was incubated with ribosomes (25 nM) for 30 min at 25°C in the buffer containing 20 mM HEPES-KOH (pH 7.5), 50 mM NH 4 Cl, 10 mM Mg(CH 3 COO) 2 , and 0.05% Tween-20.…”
Section: Methodsmentioning
confidence: 99%
“…Binding affinities of CAM-derivatives to E. coli ribosomes was analyzed by competition binding assay using fluorescently-labeled BODIPY-ERY as described before [26, 27, 37]. BODIPY-ERY (4 nM) was incubated with ribosomes (25 nM) for 30 min at 25°C in the buffer containing 20 mM HEPES-KOH (pH 7.5), 50 mM NH 4 Cl, 10 mM Mg(CH 3 COO) 2 , and 0.05% Tween-20.…”
Section: Methodsmentioning
confidence: 99%
“…Controlled dynamics and meta dynamics were calculated using the PLUMED software [45] version 1.3 that works together with the GROMACS software suite. Position and frequency of hydrogen bonds were analyzed as described earlier [33].…”
Section: Methodsmentioning
confidence: 99%
“…In particular, it revealed some potential contacts of the key amino acid residues within peptides that arrest translation with senso ry nucleotide residues of the RT [32]. Recently, using this method, we found possible reasons for abnormal biologi cal activity of peptide derivatives of macrolides, which inhibit protein synthesis, and described a novel potential site in the walls of the RT that interacts with nascent polypeptide chains [33]. By using MD simulation, we observed that the potential signal transmitting pathway A2058 C2063 behaved as a dynamic ensemble of interde pendent conformational states, wherein cascade like changes can originate.…”
mentioning
confidence: 98%
“…19,20 Specifically, molecular dynamics simulations suggest that the N-acylglycyl moiety of the aminoacylated 5-O-mycominosyl-tylonolide derivative could be positioned to form hydrogen bonds with 23S rRNA A752 and Lys 90 of ribosomal protein L22. These hydrogen bonds could potentially disrupt the essential A752:U2609 base pair, which has previously been shown to play a role in both peptide stalling and macrolide antibiotic interactions.…”
mentioning
confidence: 99%